NOTARIAL AUTHENTICATION OF RESOLUTIONS AND TRANSACTIONS IN COMMERCIAL COMPANIES AS THE ELEMENT OF PROTECTION AGAINST FORCIBLE TAKEOVER - Kaldybayev , Аскар Куралбаевич; Zhumagaliyeva , Жанна Болатовна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2021)
The author of the article analyzed the existing facts of hostile takeovers in entrepreneurship in Kazakhstan, provided references to the risks of business seizures voiced by the business community during a meeting on countering hostile takeovers, as well as noted the methods of modern raiders, which do not allow proving their involvement in “hostile takeovers”. The drawbacks of legal regulation of the current legislation of the Republic of Kazakhstan on the application of notarial form of the transaction in transactions for the alienation of shares were revealed. A conclusion is made about the representativeness of Kazakhstan's practice of prosecution for raiding, based on statistics on article 249 of the Criminal Code of the Republic of Kazakhstan “Raidership”. In this regard, the author studied the experience of the Russian Federation in terms of the introduction of the figure of the notary in corporate relations of Russian companies. Using the historical and legal method, the notary's entry into civil legal relations in Russia is examined in stages, through a description of the adopted normative legal acts and the resulting changes in the number of corporate disputes and, consequently, in the number of court cases. For which the author gives statistics of cases in arbitration courts by categories of cases arising from corporate disputes over shares, with and without the participation of a notary. The study concludes that Russia has a favorable experience in attracting the figure of the notary in the sphere of corporate life of commercial companies. Analogy of social and legal conditions for doing business in Russia and Kazakhstan has been made. The need for further detailed elaboration on the limits of notaries' participation (notarization of only the facts of corporate decisions or notarization of transactions with full absorption of the notary in the content of the transaction) and on the cost of notary fee rates were voiced. The author also noted the existing under the current law the possibility of attracting a notary in corporate relations of Kazakh commercial companies at the request of participant’s owners of shares in commercial companies to date. The author suggested that the cost of the risks associated with a possible hostile takeover of the business is many times greater than the cost of the notary fee.